KEBIJAKAN RUSIA MENERAPKAN SISTEM CASPIAN PIPELINE CONSORSIUM (CPC) DALAM KERJASAMA DIBIDANG ENERGI MIGAS DENGAN KHAZAKHSTANTAHUN 2010-2014 - Robi Agfa; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the policy of Rusia implemented the Caspian Pipeline Concorcium system in oil cooperation Rusia with Khazakhstan in 2010-2014. Oil one of most important for human and nowdays every states need a oil with politics oil. Khazakhstan are one of most country in Centre Asia Region that have big potency in oil, its make a Rusia to create a agreement wiyth Khazakahstan.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Rusia implemented the Caspian Pipeline Concorcium system in oil cooperation Rusia with Khazakhstan. The theories applied in this research are realism perspective with the foreign policy by Richard Snyder.The conclusion of this research the policy of Rusia implemented the Caspian Pipeline Concorcium system in oil cooperation Rusia with Khazakhstan are caused by strategys value of Khazakhstan for Rusia to oil supply, the needed of oil for Rusia, used for distribution of oil Rusia to another state in Center Asia region and to containment of United State hegemony in Centre Asia Region.Key words: implementation, policy, oil and trades.